Isolation and Characterization of a Myotoxic Phospholipase A2from the Venom of the Arboreal SnakeBothriechis(Bothrops)schlegeliifrom Costa Rica - Angulo Ugalde, Yamileth (1997)
A new myotoxic phospholipase A2was isolated from the venom of the arboreal snakeBothriechis schlegelii(formerlyBothrops schlegelii) from Costa Rica, by ion-exchange chromatography on CM-Sephadex.B. schlegeliimyotoxin I is a basic protein (pI> 9.3) with a subunit molecular weight of 15 kDa, which migrates as a dimer in sodium dodecyl sulfate–polyacrylamide gel electrophoresis under nonreducing conditions. This myotoxin is recognized by antibodies generated againstBothrops aspermyotoxin II (a lysine-49 phospholipase A2), by both enzyme-immunoassay and gel immunodiffusion, in the latter case with a pattern of partial identity. The toxin induces rapid myonecrosis upon intramuscular injection in mice, as evidenced by the early increase in plasma creatine kinase activity and by direct intravital microscopic observation.B. schlegeliimyotoxin I also induces edema in the mouse footpad assay and exerts lethal activity (LD50∼2.5 μg/g) upon intravenous injection. The toxin has a low phospholipase A2activity (4.2 μEq·mg−1·min−1) using egg yolk phospholipids as substrate. It also shows a weak anticoagulant effectin vitro.Its N-terminal sequence, SMYELGKMILLETGKNAATSYIAYG, shows 93% homology with bothBothrops aspermyotoxin II andB. jararacussubothropstoxin I, suggesting thatB. schlegeliimyotoxin I may be a new lysine-49 variant of this family of myotoxic phospholipases A2.